2013
DOI: 10.1002/hyp.9699
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐scale hydroclimatic analysis of runoff generation in the Athabasca River, western Canada

Abstract: Abstract:A multi-scale hydroclimatic study of runoff generation in the Athabasca River watershed located in western Canada is presented. Mann-Kendall trend detection tests performed on hydrometric data for the lower Athabasca River (LAR) revealed predominantly significant (p < 0. The results from our study demonstrated that potentially inconsistent and/or divergent trend results can be obtained when using different time periods and/or regions of the watershed, emphasizing that extreme caution should be exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 58 publications
5
41
2
Order By: Relevance
“…This includes a 37.9 % decline in streamflow for the main stem Athabasca River below McMurray (location of the furthest downstream hydrometric gauge on the river with publicly accessible hydrometric data), with substantially lesser reductions in other neighbouring rivers draining into the lake. These findings are consistent with those of other recent studies that have investigated Athabasca River streamflow trends (e.g., Schindler and Donahue, 2006;Peters et al, 2013;Bawden et al, 2014;Rood et al, 2015). Thus, our finding of a general decline Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Past Streamflow Input To Lake Athabascasupporting
confidence: 93%
“…This includes a 37.9 % decline in streamflow for the main stem Athabasca River below McMurray (location of the furthest downstream hydrometric gauge on the river with publicly accessible hydrometric data), with substantially lesser reductions in other neighbouring rivers draining into the lake. These findings are consistent with those of other recent studies that have investigated Athabasca River streamflow trends (e.g., Schindler and Donahue, 2006;Peters et al, 2013;Bawden et al, 2014;Rood et al, 2015). Thus, our finding of a general decline Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Past Streamflow Input To Lake Athabascasupporting
confidence: 93%
“…S4). The GLS trend analysis of instrumental data confirms that the PDO and the PNA, with their similar low-frequency components (28), have a significant impact on historical ARB flows (8). In the 900-y proxy flow record, the MCA spectrum contains the modes of variability typical of the PDO and the associated North Pacific Index.…”
Section: Discussionmentioning
confidence: 68%
“…4) emphasize the intraannual variability and express concern about water withdrawals in the low-flow winter season. Less attention has been given to flow variability at interannual to decadal scales associated with climate oscillations such as the Pacific Decadal Oscillation (PDO) and Pacific North American mode (PNA), which are known to have significant impacts on runoff from the Rocky Mountains, including in the ARB (6)(7)(8)(9), and the potential consequences of a long period of predominantly low flow. We investigate the response of ARB flows to the low-frequency components of the PDO and PNA.…”
mentioning
confidence: 99%
“…Major river systems such as the Mackenzie and Nelson (which includes the Saskatchewan River system) have shown no detectable long-term trends at their mouths over this time (Woo and Thorne, 2003;Déry and Wood, 2005;McClelland et al, 2006;Déry et al, 2011), while statistically significant declines in annual flow have been observed for some smaller systems within these, such as the Athabasca River and its tributaries, and other rivers draining from the eastern slopes of the southern Rocky Mountains (Burn et al, 2004b;Rood et al, 2005;St. Jacques et al, 2010;Peters et al, 2013). Seasonally, a consistent pattern of increasing flow in the winter has been reported -especially for the Mackenzie River and many of its northern tributaries -with significant trends in the annual minimum discharge and lower flow percentiles (Burn et al, 2004b;Rood et al, 2008;St.…”
Section: Changes In River Dischargementioning
confidence: 83%